PENERAPAN MODEL PEMBELAJARAN ICARE BERBANTAUN PhET SIMULASTION UNTUK MENINGKATKAN PEMAHAMAN KONSEP SISWA KELAS VIII SMP TARUNA PEKANBARU - Purba, Crisnova Genesia; Islami, Nur; Ernidawati, Ernidawati (SILAMPARI JURNAL PENDIDIKAN ILMU FISIKA, 2024)
This research aims to describe the application of the ICARE learning model assisted by PhET simulation to improve students' conceptual understanding and to determine the differences in students' conceptual understanding between classes that apply the ICARE learning model assisted by PhET simulation and classes that apply the conventional learning model in class VIII of Taruna Pekanbaru Middle School on light material. and optical instruments. This research uses a quasi-experimental research method with a nonequivalent post-test control group design. This research uses a sampling technique, namely simple random sampling. The samples in this study included Tiger Kumbang 3 class as the experimental class and Macan Kumbang 2 as the control class. The results of the descriptive analysis in the experimental class obtained an average conceptual understanding of 75.8 in the good category, while in the control class the average conceptual understanding was 63.8 in the quite good category. The hypothesis test results obtained were 0.000, which is a value smaller than 0.05. There is a significant difference in student understanding of concepts between classes that apply the ICARE learning model assisted by PhET simulation and control classes that apply conventional learning models on light and optical devices.